Gender dan Emansipasi Perempuan dalam Pendidikan Islam - Achmad Faisol Haq (Universitas Islam Lamongan, 2020)
The Islamic education problems that are often criticized by the West are gender issues, Islamic education is considered west to overrule the role of women in Islamic education, whereas in Islamic education since the beginning of Islam Strongly uphold women's standing, especially in terms of inheritance and the similarity of rights and obligations in science. In modern eras of women's emancipation movement in Islam are more likely to follow the western mindset, the activists of Islamic feminism could take a pattern of the Muslim philosopher Greek Helereism, as in classical Islam the Muslim philosopher could put aside the philosophical thought of Greek Helenism that was incompatible with the teachings of Islam, as well as to take the thought of Helenism Greek that matched the spirit of Islam. This article is an explanation of the gender movements and emancipation of women in particular in Islamic education. It is important to reconstruct the fundamentals of Islamic perspectives, because Islam has a universal view and equal rights in education between men and women is the same as other aspects and gender should be the same. Influenced by Islamic spiritual, especially in the rules of education for Muslims